RETRACTION NOTICE "Planting depth management increases early growth, aboveground biomass, and carbon storage of Eucalyptus pellita at Ultisols in South Sumatra" - Pandu Yudha Adi Putra Wirabuana; Ronggo Sadono; Sergian Juniarso (Journal of Degraded and Mining Lands Management)
This article entitled â€œPlanting depth management increases early growth, aboveground biomass, and carbon storage of Eucalyptus pellita at Ultisols in South Sumatraâ€ (2020), authored by Pandu Yudha Adi Putra Wirabuana, Ronggo Sadono, Sergian Juniarso, published in Volume 7, Issue 4. of Journal of Degraded and Mining Lands Management, pp. 2253-2261 has been retracted as requested by the authors.